Library teen advisory groups - Tuccillo, Diane P. (Rowman & Littlefield, 2018)
Teen advisory groups (TAGs) may flourish in many libraries today, but many others are newly initiating them or hoping to revitalize ones that are floundering. But even successful groups need tips and best practices to make their TAGs even better. This updated and revised second edition remains the go-to guide for planning, running, and evaluating TAGs in both school and public libraries. Its wealth of positive advice and information leads TAG teens and their peers to meaningful experiences that encourage reading, library use, and library support—into adulthood. In this indispensable guide, Diane P. Tuccillo carefully explains and explores the current, wide landscape of TAGs, covering funding to bylaws; getting a new group on its feet to rejuvenating an old one; planning traditional TAG projects to creating unique roles; and community involvement to voting on adult library boards. Vivid profiles of successful teen groups, organized into public and school library sections, tell each group’s story along with pertinent teen feedback. Sample documents covering mission statements, applications, parent permission forms, publicity flyers, and teen book review ideas, as well as evaluation advice, can be borrowed or adapted. A helpful bibliography and webliography is included. Library directors, school administrators, library educators, and librarians who work directly with teens in school and public libraries will be unable to resist such compelling testaments to the value of TAGs.--Provided by publisher.